PROFILE OF SOCIETY JORONG SIMPANG TOLANG KECAMATAN RANAH BATAHAN KABUPATEN WEST PASAMAN TO FULFILL NECESSETY IN LIFE - TAGOR, TAGOR; Ahmad, Drs. Ridwan; Yuherman, SP, M.Pd, Yuherman, SP, M.Pd (Pendidikan Geografi, 2014)
ABSTRACTThis research will be useful to describe profil of society jorong simpang tolang kecamatan ranah batahan kabupaten west pasaman to fulfill neressity in life refer to :1). Kebutuhan pangan, 2). Kebutuhan sandang, 3). Kebutuhan papan, 4). And pendidikan.This method is descriptive, population of this research is the family,s leader of society jorong simpang tolang kecamatan ranah batahan west pasaman who is unaple in fulfill necessityÂ  them life is one hundred seventy five (175) from family,s leader.data collection used questionnaire with analysis technique, use formulation presentase and Tcr.Result from research are : 1). Kebutuhan pangan from family,s leader of society jorong simpang tolang kecamatan ranah batahan kabupaten west pasaman is not good enough is 63,66% from 88 respondent.2). Kebutuhan sandang from family,s leader of society jorong simpang tolang kecamatan ranah batahan kabupaten west pasaman is not good enough is 62,05% from 88 respondent. 3). Kebutuhan papan from family,s leader of societyÂ  jorong simpang tolang kecamatan ranah batahan kabupaten west pasaman good enaugh is 72,2% from 88 respondent. 4). Kabutuhan pendidikan from family,s leader of society jorong simpang tolang kecamatan ranah batahan kabupaten west pasaman good enough is 78,92% from 88 respondent.